EFL teachers' perception about implementing active learning techniques in teaching speaking : - Ho, Xuan Huong (Can Tho University, 2019)
The present research was conducted to obtain two research aims. The first aim is to find out teachers’ perceptions about active learning techniques in teaching speaking. The second aim is to investigate the benefits and difficulties teachers face when they implemented active learning techniques in their speaking classrooms. The following hypotheses have been established: The teachers’ perceptions about active learning techniques are somewhat high;The teachers reveal the advantages and disadvantages when implementing active learning techniques in their speaking classrooms and recommend some adaptations and solutions to enhance their teaching experiences